CONTINUOUS TIME MARKOV MODEL OF KANJI DAM WATER OUTFLOW AS A PANACEA TO FLOODING IN NIGERIA - Abdullahi, Mohammed; Adamu, Lawal (FUDMA JOURNAL OF SCIENCES, 2025)
This paper examines the application of a continuous time Markov model with non-stationary transition probabilities to study the water outflow level of Kainji Dam. The results show that state 2 (Medium water outflow) has the optimal water outflow of about 36%. This consolidates the reality on the phenomenon that the water outflow stays in state 2 (Medium outflow) most of the time and in other states some other time. Also, High water outflow is obtained for about 32%, which shows that flooding is not occur every year in Kainji hydroelectric Dam. These variations of the water outflow directly affect the hydroelectric power generation, periodic floods experienced, and availability of other dam resources. Continuous-time Markov model could be used as a predictive technique for studying the reservoir outflow of the Kainji Hydro Dam. These projections might be useful for the management of the dam resources, readiness and control of periodic floods being experienced in this era in Nigeria.